Slit-lamp biomicroscopy in primary eye care - Mondal, Biswajit (New Delhi : Jaypee-Highlights, 2013)
There continues to be an explosion of research on issues of diagnosis/diagnostic methods in primary eye care. It is important to introduce the simple way of diagnosis to the students and clinicians in the field of primary eye care. This first edition of Slit-lamp Biomicroscopy in Primary Eye Care addresses these concepts and provides information for students and clinicians, who need a ready source of information regarding slit-lamp and its application in primary eye care.
Contents 1. Overview 2. Parts of the slit-lamp biomicroscope 3. Magnification ranges and application 4. Filters and accessories 5. Instrument adjustment and positioning the patient in the slit-lamp y otros
Keywords: CÓRNEA -- ENFERMEDADES; OFTALMOLOGIA; Cornea -- Diseases